Effect of long-acting β-agonists/glucocorticoids on human airway epithelial cell cytokine, transcriptomic and oxidative stress responses to cannabis smoke - Huff, Ryan D.; Aguiar, Jennifer A.; Tse, Wayne; Stämpfli, Martin R.; McConkey, Brendan J.; Doxey, Andrew C.; Hirota, Jeremy A. (ERJ open research, 2020)
LABA/GC intervention in airway epithelial cells exposed to cannabis smoke reduces levels of pro-inflammatory (CXCL8) and antiviral (CXCL10) mediators, while transcriptomic signatures of neutrophil-mediated immunity and oxidative stress remain elevated http://bit.ly/2qiSQhH.LABA/GC intervention in airway epithelial cells exposed to cannabis smoke reduces levels of pro-inflammatory (CXCL8) and antiviral (CXCL10) mediators, while transcriptomic signatures of neutrophil-mediated immunity and oxidative stress remain elevated http://bit.ly/2qiSQhH.